Pengaruh Bauran Komunikasi Pemasaran terhadap Keputusan Pembelian Batu Tela: pada UMKM Material Bangunan di Kabupaten Jayapura - Supriyanto Supriyanto; Dian Ferriswara; Sarwani Sarwani; Galuh Ajeng Ayuningtiyas (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study was conducted with the aim of identifying the extent to which the marketing communication mix influences the purchasing decisions of Batu Tela products in building material MSMEs operating in Jayapura Regency. The marketing communication mix examined in this study includes five main elements, namely advertising, sales promotion, publicity, personal selling, and direct marketing. These five elements are considered important factors that can influence how consumers recognize, evaluate, and ultimately make decisions to purchase the products offered. The research method used is a quantitative approach with a survey technique. The research respondents were 60 consumers selected with the criteria of having purchased Batu Tela products at least once in the last six months. The collected data were then analyzed using multiple linear regression methods to determine the relationship and influence of each marketing communication element on purchasing decisions. The results of the study indicate that all five marketing communication elements have been proven to have a significant influence on consumer purchasing decisions. This confirms that the marketing communication strategy designed and implemented by MSMEs plays an important role in building positive consumer perceptions and encouraging purchase transactions. Of all the variables studied, sales promotion emerged as the dominant factor that most strongly influenced consumer decisions. Incentives in the form of price cuts, discounts, and special offers are considered more effective in attracting consumer attention and interest than other elements. This finding provides practical implications: MSMEs need to design more integrated marketing communications strategies, emphasizing creative and sustainable sales promotion programs. Furthermore, this research opens up opportunities for further research by expanding the variables, particularly internal consumer factors that can influence decision-making.